2021
DOI: 10.1101/2021.04.20.440698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-structural carbohydrate concentrations in woody organs, but not leaves, of temperate and tropical tree angiosperms are independent of the ‘fast-slow’ plant economic spectrum

Abstract: SummaryBackground and AimsCarbohydrate reserves play a vital role in plant survival during periods of negative carbon balance. Considering active storage of reserves, there is a trade-off between carbon allocation to growth and to reserves and defense. A resulting hypothesis is that allocation to reserves exhibits a coordinated variation with functional traits associated with the ‘fast-slow’ plant economics spectrum.MethodsWe tested the relationship between non-structural carbohydrates (NSC) of tree organs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
(136 reference statements)
1
0
0
Order By: Relevance
“…This finding is partly consistent with those found by Ramirez et al. (2021), who showed that the position of tree species along the plant acquisition and conservative strategy spectrum was a predictor of NSC in leaves, but not in stems and coarse roots. Additionally, we also showed that leaf NSC augmented with increasing leaf N and decreasing LMA, suggesting that species with an acquisitive resource strategy could accumulate more NSC in their leaves than those with a conservative resource strategy.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is partly consistent with those found by Ramirez et al. (2021), who showed that the position of tree species along the plant acquisition and conservative strategy spectrum was a predictor of NSC in leaves, but not in stems and coarse roots. Additionally, we also showed that leaf NSC augmented with increasing leaf N and decreasing LMA, suggesting that species with an acquisitive resource strategy could accumulate more NSC in their leaves than those with a conservative resource strategy.…”
Section: Discussionsupporting
confidence: 92%